Influence of the Top Dielectric Layer on Interdigitated Capacitive Dew Point Detector Operation. (2015) - Jachowicz, Ryszard; Tarapata, Grzegorz; Paczesny, Daniel; Urban, Gerald; Bergmann, Michael
Abstract: The paper reports an influence of protective dielectric film deposited on the detector surface on its sensitivity on water dew presence, its stability and parameters repeatability. For the tests of all types of coatings the special measurement stand with full computer control has been constructed. The results of the tests have been of the highest importance for successful Dew Point Hygrometer (DPH) operation with capacitive dew detection.